1999
DOI: 10.1046/j.1365-2222.1999.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to the pine processionary caterpillar (Thaumetopoea pityocampa)

Abstract: Allergic reactions to T. pityocampa urticating hairs have different clinical characteristics than those induced by a toxic-irritative mechanism and are more frequent than suspected. Allergic reactions to this caterpillar among occasional visitors to pine-wood areas, and particularly in pine-forest workers, should be taken into consideration by allergists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 11 publications
4
75
1
5
Order By: Relevance
“…It was shown that this protein activates mast cells via a direct non-immunological effect (non-IgE-mediated mediator release) and a type I allergic hypersensitivity reaction (IgE-mediated mediator release) [12]. The existence of a (true) type I allergic hypersensitivity reaction to the larval extracts of the pine processionary caterpillar [12, 13, 14]and the oak processionary caterpillar [12]was confirmed by positive skin prick tests and the determination of specific IgE antibodies. Mechanical irritation from penetration of the setae (foreign body reaction) appears to be a third mechanism which is responsible for the reactions in skin and mucous membranes [10, 11, 12, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this protein activates mast cells via a direct non-immunological effect (non-IgE-mediated mediator release) and a type I allergic hypersensitivity reaction (IgE-mediated mediator release) [12]. The existence of a (true) type I allergic hypersensitivity reaction to the larval extracts of the pine processionary caterpillar [12, 13, 14]and the oak processionary caterpillar [12]was confirmed by positive skin prick tests and the determination of specific IgE antibodies. Mechanical irritation from penetration of the setae (foreign body reaction) appears to be a third mechanism which is responsible for the reactions in skin and mucous membranes [10, 11, 12, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Setae can also be present in the air, as shown by techniques used to detect pollen or airborne microorganisms. The abundance of these hairs in the air depends on the distance from areas with contaminated pines, weather conditions and stage in the biological cycle.…”
Section: Biologymentioning
confidence: 99%
“…The occupations at greater risk are pine cone collectors and lumberjacks, followed at some distance by resin collectors, farmers, forest wardens, gardeners, bricklayers, and haulage contractors who work in regions of pine forest. [11][12][13][14] Children are another risk group, most likely because their natural curiosity leads them to touch the caterpillars or play with sand or vegetation that has these larvae. 15,16 Symptoms may occur with the start of the pruning season and pine cone collection in the fall, or wood and sand collection in summer months.…”
Section: Epidemiologymentioning
confidence: 99%
“…Nei soggetti allergici compaiono, oltre a quanto descritto in precedenza per i soggetti normali, reazioni IgE mediate che vanno dalle più semplici reazioni LLR ai vari gradi di anafilassi sistemica. Le reazioni allergiche maggiormente diffuse restano comunque l'orticaria generalizzata e l'angioedema [14][15][16] . Il trattamento medico è necessario nella maggior parte dei contatti e richiede:…”
Section: Le Ep Pi Id Do Ot Tt Te Er Ri Iunclassified